Pre- and Postoperative Capecitabine Without or With Oxaliplatin in Locally Advanced Rectal Cancer: PETACC 6 Trial by EORTC GITCG and ROG, AIO, AGITG, BGDO, and FFCD. Issue 1 (1st January 2021) - Schmoll, Hans-Joachim; Stein, Alexander; Van Cutsem, Eric; Price, Timothy; Hofheinz, Ralf D.; Nordlinger, Bernard; Daisne, Jean-François; Janssens, Jos; Brenner, Baruch; Reinel, Hans; Hollerbach, Stephan; Caca, Karel; et al.
Abstract : PURPOSE: The PETACC 6 trial investigates whether the addition of oxaliplatin to preoperative capecitabine-based chemoradiation and postoperative capecitabine improves disease-free survival (DFS) in locally advanced rectal cancer. METHODS: Between November 2008 and September 2011, patients with rectal adenocarcinoma within 12 cm from the anal verge, T3/4 and/or node positive, were randomly assigned to 5 weeks preoperative capecitabine-based chemoradiation (45-50.4 Gy) followed by six cycles of adjuvant capecitabine, both without (control arm, 1) or with (experimental arm, 2) oxaliplatin. The primary end point was improvement of 3-year DFS by oxaliplatin from 65% to 72% (hazard ratio [HR], 0.763). RESULTS: A total of 1, 094 patients were randomly assigned (intention to treat), and 1, 068 eligible patients started their allocated treatment (arm 1, 543; arm 2, 525), with completion of protocol treatment in 68% (arm 1) v 54% (arm 2). A higher rate of grade 3/4 adverse events was reported in the experimental arm (14.4% v 37.3% and 23.4% v 46.6% for neoadjuvant and adjuvant treatment, respectively). At a median follow-up of 68 months (interquartile range, 58-74 months), 157 and 156 DFS events were observed in arms 1 and 2, respectively (adjusted HR, 1.02; 95% CI, 0.82 to 1.28; P = .835). Three-year DFS rate was not different, with 76.5% (95% CI, 72.7% to 79.9%) in arm 1, which is higher than anticipated, and 75.8% (95% CI, 71.9% to 79.3%) in arm 2. The 7-year DFS and overall survival (OS) rates were not different as well, with DFS of 66.1% v 65.5% (HR, 1.02) and OS of 73.5% v 73.7% (HR, 1.19) in arms 1 and 2, respectively. Subgroup analyses revealed heterogeneity in treatment effect according to German versus non-German site location, without detectable confounding factors in multivariable analysis. CONCLUSION: The addition of oxaliplatin to preoperative capecitabine-based chemoradiation and postoperative adjuvant chemotherapy impairs tolerability and feasibility and does not improve efficacy.